VD_FINDINFO HC / 2015 / 800 vom 18. September 2015 - VD Tribunal cantonal (2015)
TRANSACTION EXTRAJUDICIAIRE, FRAISEN GÉNÉRAL, DÉPENS | 105 CPC (CH), 106 al. 2 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)